Cloud Computing: Security with Educational Usage - Agrawal, Reeya; Bansal, Saloni (Journal of ISMAC, 2022)
Cloud computing is one of the latest patterns of computing, where virtualized and dynamically scalable methods are provided to the Internet as a resource. Many industrialists say that cloud computing will give a new shape to ICT companies as revolution. The security provided by cloud computing is the key concern among consumers with its beneficial widespread applications. In this paper, several latest technologies of cloud computing and security of cloud computing with its usage in education have been studied.
Keywords: Cloud computing; emerging technologies; security; SWOT